RE-ORIENTATION OF WORKERS TOWARDS RETIREMENT AS A COUNSELLING TECHNIQUE TO CURB STRESS - Awoniyi, Gideon Funmilayo (Sokoto Educational Review, 2011)
The paper sought to determine the relationship between the re-orientation of workers towards retirement and counselling technique to curb stress. The purpose was to determine whether workers actually saw the need for r re-orientation towards retirement in view of this, the paper starts with the meaning of retirement, retirement typologies, effects of retirement on retirees, the need for r retirement, management of stress in retirees for a meaningful and active retirement.